Mitigating Ammonia Emissions and Enhancing Litter Quality in Commercial Broiler Chickens using Chemically Treated Litter during the Winter Season - V Patel, Jigar; M Trivedi, Manoj; J Modi, Rakesh; M Rajpura, Rais; P Madhavatar, Mahesh (Indian Journal of Veterinary Sciences and Biotechnology, 2025)
The experiment was conducted to mitigate ammonia emissions and enhance litter quality in commercial broiler chickens using chemically  treated litter during the winter season (December-January, 2020-2021) in Anand, Gujarat. A total of 144 straight-run, day-old commercial  broiler chicks were randomly distributed into six treatment groups. Each treatment group consisted of four replicates, each with six  chicks, leading to 24 chicks per treatment. The six treatments used were: T1 - rice husk litter material (control group); T2 – husk treated  with alum @ 90 g/sq.ft.; T3 - husk treated with boric acid (H3BO3) @ 24 g/sq.ft.; T4 - husk treated with sodium bisulfate (NaHSO4) @ 25 g/ sq.ft.; T5 - husk treated with a commercially available probiotic product @ 1 g/sq.ft.; T6 - husk treated with a commercially available Yucca  schidigera liquid solution @ 1.0 mL/sq.ft. The litter treatment (T2 to T6) was applied on the 1st, 15th, and 29th days of the experiment. The  study evaluated litter pH, moisture (%), nitrogen, and ammonia emissions (ppm) at the 6th week of age across different treatments in  experiments. Results showed significantly lower pH, moisture, and ammonia emissions in T2, with the lowest ammonia levels observed  in T2 (P
Keywords: Ammonia emission; Broiler chicken; Commercial; Litter treatment; Litter quality